Measurement of Financial Performance Using the Concept of Value for Money in The Government of Bandung City - Ratumas Resa Anggia Sakti (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
In the context of transparency and accountability of public money management, the Bandung City Government uses a tool called e-budgeting. Not only has the objectives of transparency and accountability, but the use of a budget formulation application system using e-budgeting is also expected to be able to improve the government's financial performance to be more economical, efficient, and effective. This study aims to measure the financial performance of the Bandung City Government before and after the use of e-budgeting using the concept of value for money for the 2014-2019 fiscal year. Data analysis used descriptive analysis with quantitative research methods. The results of the study are based on the Analysis of the Bandung City Government Budget Realization Report for the 2014-2016 fiscal year (before the use of e-budgeting) using the concept of Value for money, Bandung City Government financial performance shows economic criteria (78.72%), inefficient (98.04%) and effective (90.65%). Meanwhile, for the 2017-2019 fiscal year (after the use of e-budgeting) the financial performance of the Bandung City Government shows economic criteria (83.39%), inefficient (99.48%), and quite effective (88%).